The impact of education: on character formation, ethics, and the communication of values in late modern pluralistic societies - Witte, John; Welker, Michael; Pickard, Stephen K. (Evangelische Verlagsanstalt, 2022)
Frontmatter -- Cover -- Titel -- Impressum -- Inhalt -- Acknowledgements -- Preface to the Series -- Introduction -- Part One: Society, Values, and Character -- What Has Solomon to Do with Google? Old Testament Wisdom Literature and the Mediation of Truth in Modern Pluralistic Societies -- Character Socialization and Diversity in Modern Democracies Today -- Character Formation from a Psychological Point of View: Search for Values, Search for Sinn -- Civic Norms and Distinctive Convictions: Finding the Right Balance -- Part Two: National Contexts -- Restoring the Value(s) of Religion in American Public Education -- Stabilizing Continuity and Transforming Spirituality: Germany's Democratization after 1945 as an Example of the Impact of Education on Character Formation, the Communication of Values, and the Breakdown of Totalitarianism -- School Education in Australia: Building Character and Reforming the Nation -- An Analysis of the Impact of the Korean Education System on the Character, Ethics, and Values of Koreans and Its Implications for Late Modern Pluralistic Societies -- Public Education and Moral Formation in the United States: A View from the Early Twenty-First Century -- Part Three: Emerging Themes -- Vocational Exploration as Character Formation: A New Direction for Higher Education -- Character Formation and Literarische Bildung: Aims and Potentials in Literature Education -- Resetting Baselines for an Earth-Centered Moral Education -- Backmatter -- Contributors.
Description based on publisher supplied metadata and other sources
Keywords: Aufsatzsammlung; Bildung; Religionssoziologie